Hubungan Antara Frekuensi Mengikuti Pelatihan dengan Tingkat Kompetensi Pedagogik Guru Pendidikan Anak Usia Dini - Dimas Putra putra (ABNA : Journal of Islamic Early Childhood Education, 2021)
The problem in this study is that the teacher's ability to manage student learning is still not in accordance with the mastery of pedagogic competencies. This study aims to determine the relationship between the frequency of training and the level of pedagogic competence of PAUD teachers. This type of research is descriptive correlational, in April – August 2020 with a population of 80 and a sample of 67 PAUD teachers in Simo, Boyolali. using a questionnaire. normality test, analyzed using Spearman Rho. The results: (1) The frequency of attending PAUD teacher training is in the medium category (55.2%), (2) The level of pedagogic competence of PAUD teachers is in the medium category (56.7%) and ( 3) there is a significant positive relationship between the frequency of training and the level of pedagogical competence of teachers (r = 0.789; p value = 0.000 < 0.05)